Implementing Introductory Training in Trauma-Informed Care Into Mental Health Rehabilitation Services: A Mixed Methods Evaluation - Nation, Laura; Spence, Nicola; Parker, Stephen; Wheeler, Maddison Paige; Powe, Kate; Siew, Mei; Nevin, Tamara; McKay, Michelle; White, Michelle; Dark, Frances Louise (Frontiers in Psychiatry, 2022)
Objective: Describing the implementation of training in trauma-informed care (TIC) across a mental health rehabilitation service. Method: A mixed-methods approach was applied, this incorporated baseline measures of staff attitudes towards TIC, quantitative description of staff training participation, and semi-structured interviews of Team Leaders' views on the implementation of TIC. Results: Fifty-five of 123 staff responded to the OCRA survey (44.7%). Training completion varied considerably between the teams (4.8% to 78%). Analysis of the Team Leader interviews identified four broad themes: The need to respect the person’s life journey including the risk of re-traumatisation; the importance of considering the context of implementing TIC training; TIC being an essential part of mental health care, and staff may also have trauma histories. Conclusions: Staff working in mental health rehabilitation are supportive of the need for TIC. The variable training uptake did not reflect the staffs’ reported importance of TIC. The burden of adjusting mental health care delivery to COVID-19 restrictions was reported as a major influence on the uptake of training. Systematically implementing training in TIC is essential but needs to be complemented by routine service processes that aid the operationalization of this approach into daily mental healthcare delivery.